2005
DOI: 10.1242/dev.01613
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of a long-range cis-regulatory module causes complete loss of limb-specificShhexpression and truncation of the mouse limb

Abstract: Mutations in a conserved non-coding region in intron 5 of the Lmbr1 locus, which is 1 Mb away from the sonic hedgehog(Shh) coding sequence, are responsible for mouse and human preaxial polydactyly with mirror-image digit duplications. In the mouse mutants,ectopic Shh expression is observed in the anterior mesenchyme of limb buds. Furthermore, a transgenic reporter gene flanked with this conserved non-coding region shows normal polarized expression in mouse limb buds. This conserved sequence has therefore been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
334
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(343 citation statements)
references
References 26 publications
3
334
1
2
Order By: Relevance
“…That epigenetic changes can control development and disease is well accepted (see recent reviews: Rajasekhar and Begemann, 2007;Soshnikova and Duboule, 2008); therefore, it is reasonable to believe that epigenetic mechanisms will also play a role in regeneration. Yakushiji et al (2007) studied the methylation level of the enhancer region of a limb-specific shh enhancer, which has been conserved from fish to mammals (Sagai et al, 2005), in amphibians with different regenerative abilities. In Xenopus hindlimbs that regenerate and express shh, the enhancer was methylated on approximately half the CpG sites (40 -50%) in either developing or regenerating limbs, while in the pattern-deficient regenerating froglet forelimb, it was hypermethylated (84 -91%).…”
Section: Epigeneticsmentioning
confidence: 99%
“…That epigenetic changes can control development and disease is well accepted (see recent reviews: Rajasekhar and Begemann, 2007;Soshnikova and Duboule, 2008); therefore, it is reasonable to believe that epigenetic mechanisms will also play a role in regeneration. Yakushiji et al (2007) studied the methylation level of the enhancer region of a limb-specific shh enhancer, which has been conserved from fish to mammals (Sagai et al, 2005), in amphibians with different regenerative abilities. In Xenopus hindlimbs that regenerate and express shh, the enhancer was methylated on approximately half the CpG sites (40 -50%) in either developing or regenerating limbs, while in the pattern-deficient regenerating froglet forelimb, it was hypermethylated (84 -91%).…”
Section: Epigeneticsmentioning
confidence: 99%
“…A common theme is emerging that genes that are elaborately regulated during development are often controlled by modular cis-acting elements at a great distance from the start site of transcription. Studies in transgenic mice have revealed a spectrum of regulatory strategies that may be in effect: distant and scattered over a large interval (Biben et al, 1996;Moore et al, 1998;Antes et al, 2001;Mortlock et al, 2003), far 3Ј of the gene (DiLeone et al, 1998;Pape et al, 1999), intronic (Rowntree et al, 2001), or even embedded in neighboring genes (Carvajal et al, 2001;Sagai et al, 2005). Attempts to identify gene regulatory regions can be speeded significantly by use of bioinformatics tools to locate evolutionarily conserved noncoding sequences among species.…”
Section: Dommentioning
confidence: 99%
“…Several proximal regulatory element knockouts have been generated in mice including the Hif1␣ response element of VEGF-A (38) and a CArG box upstream of the Telokin gene (39). A distal CRM of Shh, located nearly 1 megabase away from its promoter, has also been deleted in its native genomic context and shown to be essential for normal Shh expression (40). On the other hand, there have been some regulatory element knockouts with unpredictable outcomes.…”
Section: Remote Control Of Gene Expression Revealed By Comparative Gementioning
confidence: 99%